Safety of Surgery After Rituximab Therapy in 133 Patients With Rheumatoid Arthritis: Data From the AutoImmunity and Rituximab Registry. Issue 11 (28th October 2013) - Godot, S.; Gottenberg, J.‐E.; Paternotte, S.; Pane, I.; Combe, B.; Sibilia, J.; Flipo, R.‐M.; Schaeverbeke, T.; Ravaud, P.; Toussirot, E.; Berenbaum, F.; Mariette, X.; et al.
<x xml:space="preserve">Abstract</x> Objective We used data from the AutoImmunity and Rituximab (AIR) registry to investigate the safety of surgery for patients with rheumatoid arthritis receiving rituximab (RTX) in routine care. Methods Data for patients included in the AIR registry and undergoing surgery during the year following an infusion of RTX were reviewed to describe the frequency of postsurgical complications, compare patients with and without complications, and identify factors associated with complications. Results We examined data for 133 patients with a known date of surgery and at least 1 followup visit, corresponding to 140 procedures, including 94 orthopedic surgeries (67%) and 23 abdominal surgeries (16.5%). The median delay between surgery and the last RTX infusion was 6.4 months (interquartile range 4.3–8.7 months), without any difference between patients with and without complications. Nine patients (6.7%) experienced 12 complications (8.5%), including 8 surgical site infections (5.7%) and 1 death due to septic shock. Postoperative complications occurred after 4.3% of abdominal surgeries (1 of 23) and 7.4% of orthopedic surgeries (7 of 95). On univariate analysis, spine surgery was associated with postoperative complications (P = 0.048). Conclusion In common practice, the risk of complications may be more important in case of spine surgery, but does not seem to be linked to the time between the last RTX infusion and surgery.